Toward a New Vision of Informants: A History of Abuses and Suggestions for Reform - Zimmerman, Clifford S. (1994)
Informants have long been used in American criminal law enforcement. Informants are often the best, if not the only, way to discover and thwart certain crimes, particularly crimes in which the victim is unknown or reluctant to cooperate. Because of informants' usefulness, law enforcement personnel, from prosecutors to prison guards, are tempted to abuse the informant system. No government can be supposed to have expressly instructed its spies to instigate the perpetration of crime. Nevertheless, to remain unsuspected, every spy must be zealous in the cause which he pretends to have espoused. That zeal directly encourages crime. In short, our government is incidentally advancing crime while trying to curtail it, and it is doing so without bearing any responsibility. This article argues that the key to stopping the abuses of the informant relationship is to apply a rebuttable presumption that informant conduct is state action and action under color of law. This presumption will instill responsibility in law enforcement agencies for their decision to use informants. The closer informant-handler relationship will have a significant impact upon how courts view informants in both criminal and civil litigation. In both contexts, the presumption creates a linkage between the government and the informant that will force law enforcement to take responsibility for the use of informants